2010
DOI: 10.5483/bmbrep.2010.43.12.807
|View full text |Cite
|
Sign up to set email alerts
|

ZAS3 represses NFκB-dependent transcription by direct competition for DNA binding

Abstract: NFκB and ZAS3 are transcription factors that control important cellular processes including immunity, cell survival and apoptosis. Although both proteins bind the κB-motif, they produce opposite physiological consequences; NFκB activates transcription, promotes cell growth and is often found to be constitutively expressed in cancer cells, while ZAS3 generally represses transcription, inhibits cell proliferation and is downregulated in some cancers. Here, we show that ZAS3 inhibits NFκB-dependent transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
4
6
0
Order By: Relevance
“…These results suggest that ZAS3 enhances TNFα-induced apoptosis through repressing the transcription of TRAF1 and TRAF2 activated by NFκB. In line with this, our previous data showed that ZAS3 can compete for the κB DNA binding motif with NFκB (21). Taken together, our results strengthen the notion that ZAS3 inhibits NFκB-dependent expression of anti-apoptotic genes by directly competing for the κB-motif.…”
Section: Zas3 Represses Expression Of Traf1 and Traf2 To Promote Tnfαsupporting
confidence: 81%
See 3 more Smart Citations
“…These results suggest that ZAS3 enhances TNFα-induced apoptosis through repressing the transcription of TRAF1 and TRAF2 activated by NFκB. In line with this, our previous data showed that ZAS3 can compete for the κB DNA binding motif with NFκB (21). Taken together, our results strengthen the notion that ZAS3 inhibits NFκB-dependent expression of anti-apoptotic genes by directly competing for the κB-motif.…”
Section: Zas3 Represses Expression Of Traf1 and Traf2 To Promote Tnfαsupporting
confidence: 81%
“…interacted with p65, p50 or the heterodimer of p65 and p50 (Fig. 3), which is consistent with the previous result that DNA-protein complexes with intermediate gel mobility between fusion proteins of ZAS3 and NFκB do not form in electrophoretic mobility shift assay (21).…”
Section: Zas3 Neither Directly Associates With Nfκb Nor Affects Nuclesupporting
confidence: 81%
See 2 more Smart Citations
“…Sna is a short-range repressor with a zinc-finger motif that can mediate either quenching or direct repression of the transcription complex (15)(16)(17)(18). A 2.2-kb genomic region upstream of a sim early promoter includes five Sna-binding sites (12) (Fig.…”
Section: Snail-binding Sites Proximal To a Sim Early Promoter Mediatementioning
confidence: 99%